Integration of metal-organic framework with a photoactive porous-organic polymer for interface enhanced phototherapy. (March 2020) - Zheng, Xiaohua; Wang, Lei; Guan, Yuyao; Pei, Qing; Jiang, Jian; Xie, Zhigang
Abstract: Porphyrin-based porous organic polymers are highly potential candidates for cancer theranostics. However, un-controllable particle size and unclear photoactive mechanisms have been deemed to be "Achilles' heels" for their biomedical application. Herein, a facile self-template strategy has been applied to integrate two types of porous materials to build the MOF@POP-PEG nanocomposite (named HUC-PEG). As-synthesized HUC-PEG exhibited controllable particle shape and size, good biocompatibility, and better colloidal stability. Importantly, synergy "0 + 1 > 1" interface effects have been demonstrated to simultaneously enhance both the generation of more singlet oxygen ( 1 O2 ) for photodynamic therapy (PDT) and local hyperthermia for photothermal therapy (PTT), thus to achieve favorable proliferation inhibition of tumor cell both in vitro and in vivo. Moreover, the strong X-ray attenuating ability of Hf element and excellent photothermal conversion efficacy endow this nanocomposite with computed tomography (CT)/photothermal imaging functions. We believe that our ingenious design may open a new horizon for the preparation of nanoscale POP-based therapeutic agents and also realize a paradigm shift in the understanding of photoactive mechanism in porous materials.